Wellness without fairness: The missing link in psychology - Prilleltensky, Issac (2013)
To promote human welfare, psychologists must advance two important goals: wellness and fairness. Hitherto, research on wellness or well-being has discovered connections among overall satisfaction with life and important facets of life, such as relationships, income, and physical health, but the connections among various types of wellness and specific aspects of fairness remain obscure. Research on justice in psychology, in turn, has focused largely on the impact of distributive, procedural, and interactional justice on job performance and not so much on wellness outcomes. I argue that psychologists must explore in depth the association among various types of wellness, such as interpersonal, occupational, physical, and psychological, and diverse kinds of fairness, such as distributive, procedural, interpersonal, cultural, developmental, retributive, and intrapersonal. The pursuit of wellness without fairness will not yield the outcomes individuals and communities need. We must make more explicit the relationship between justice or injustice and flourishing in life.